ANALISIS DAMPAK PENERAPAN SISTEM E-COMMERCE TERHADAP PENGENDALIAN INTERNAL PERUSAHAAN SEBAGAI AKIBAT PERKEMBANGAN TEKNOLOGI INFORMASI - Dina, Wildah Akmala (Jurnal Akuntansi AKUNESA, 2013)
Internet is one of the impact of developments in information technology that has a very wide range with low marketing costs. Companies can leverage this ability to interact with customers all over the world without worrying about incompatibility sistem problem occurs on both sides. Sistem of e-commerce has changed the way companies to doing transaction and connect with their business partners. Some issues such as security and authenticity of transactions that used to seem simple in the traditional trading sistem become very complex. In e-commerce, such issues known as confidentiality, integrity, authentication, non-repudiation. In the e-commerce business across transactions are done electronically and partly owned companies accounting information sistem can also be accessed by outsiders, so that it had an impact on internal controls. The impact of e-commerce in the internal control raises new issues on the validity of the transaction, the transaction authorization and security assets that the company needed to do general controls and application controls. Keyword : information technology, e-commerce, internal controls